Exploring approaches and solutions for urban safety: a focus on women - Stiuso, Tonia (TeMA - Journal of Land Use, Mobility and Environment, 2024)
Starting from the relationship between urban planning and mobility management, TeMA has gradually expanded the view of the covered topics, always remaining in the groove of rigorous scientific in-depth analysis. This section of the Journal, Review Notes, is the expression of continuously updating emerging topics concerning relationships between urban planning, mobility, and environment, through a collection of short scientific papers written by young researchers. The Review Notes are made of five parts. Each section examines a specific aspect of the broader information storage within the main interests of TeMA Journal. In particular, this section focuses on the challenges that urban planning commonly faces in the context of urban safety, providing food for thought to readers and fellow researchers. This contribution aims to examine these challenges and the solutions proposed in the scientific literature, specifically in books, journals, and reports. For the first issue of TeMA Journal volume no. 17, this section is dedicated at identifying the gaps between the theoretical scientific progress and their actual practical implementation.